The effects of organizational politics on employees performance: The role of emotional intelligence and spirituality - Vimala, Venugopal (2013)
Organizational politics has become a common life experience in numerous corporations across the globe whereas, the concept of organizational politics has become a recent topic of debate in modern management literatures. Existing literatures suggest that the perception of organizational politics negatively influence employees’ performance in the workplace, and these negative influences can be reduced by numerous mitigating factors. The main purpose of this research “To evaluate if the impacts of perceived organizational politics are negatively imposed on job performance, and the roles of emotional intelligence and workplace spirituality in mitigating these impacts.”This research is primary based; with data for prove of hypotheses gathered via online survey. The choice of online survey is to offer responders from all over the world to participate in contributing to the overall quality of the research. The gathered data were analyzed with SPSS – factor analysis and multivariate regressions were conducted to prove the hypotheses. The analyzed data revealed that organizational politics influences job performance negatively and that these influence can be mitigated by employees’ level of emotional intelligence and workplace spirituality. Besides providing evidence to support the research topic and meeting the research objectives, it was also found that employees’ wage does not depend on their type of job (whether part-time or full-time), and that older employees are more likely to be working on full-time job than younger employees. The findings offer important implications for the support of theories on organizational politics and job performance, and how emotional intelligence and workplace spirituality help to mitigate these issues